Multi-walled carbon nanotubes promote the accumulation, distribution, and assimilation of 15N-KNO3 in Malus hupehensis by entering the roots - Shi, Junyuan; Xun, Mi; Song, Jianfei; Li, Jiaqi; Zhang, Weiwei; Yang, Hongqiang (Frontiers in Plant Science, 2023)
Multi-walled nanotubes (MWCNTs) consist of multiple rolled layers of graphene. In this study, the woody plant Malus hupehensis seedlings were used as plant materials, the distribution of MWCNTs in the roots was observed, and the effects of MWCNTs on the accumulation, distribution, and assimilation of nitrate by the seedlings were explored. The results showed that MWCNTs could penetrate the roots of Malus hupehensis seedlings, and the 50, 100, and 200 µg·mL-1 MWCNTs significantly promoted the root growth of seedlings, increased root number, root activity, fresh weight, and nitrate content of seedlings, and also increased nitrate reductase activity, free amino acid, and soluble protein content of roots and leaves. 15N tracer experiments indicated that MWCNTs decreased the distribution ratio of 15N-KNO3 in Malus hupehensis roots but increased its distribution ratio in stems and leaves. MWCNTs improved the utilization ratio of 15N-KNO3 in Malus hupehensis seedlings, with the values being increased by 16.19%, 53.04%, and 86.44% following the 50, 100, and 200 µg·mL-1 MWCNTs, respectively. The RT-qPCR analysis showed that MWCNTs significantly affected the expression of genes (MhNRTs) related to nitrate uptake and transport in roots and leaves, and MhNRT1.4, MhNRT1.7, MhNRT1.8, MhNRT2.1, MhNRT2.5, and MhNRT2.7 were notably up-regulated in response to 200 µg·mL-1 MWCNTs. Raman analysis and transmission electron microscopy images indicated that MWCNTs could enter the root tissue of Malus hupehensis and were distributed between the cell wall and cytoplasmic membrane. Pearson correlation analysis showed that root tip number, root fractal dimension, and root activity were the main factors affecting root uptake and assimilation of nitrate. These findings suggest that MWCNTs promoted root growth by entering the root, stimulated the expression of MhNRTs, and increased NR activity, thereby enhancing the uptake, distribution, and assimilation of nitrate by root, and ultimately improved the utilization of 15N-KNO3 by Malus hupehensis seedlings.